In vivo and in situ synchrotron radiation-based [mu]-XRF reveals elemental distributions during the early attachment phase of barnacle larvae and juvenile barnacles - Senkbeil, Tobias; Mohamed, Tawheed H. A. (Analytical and bioanalytical chemistry, 2016)
Barnacles are able to establish stable surface contacts and adhere underwater. While the composition of adult barnacle cement has been intensively studied, far less is known about the composition of the cement of the settlement-stage cypris larva. The main challenge in studying the adhesives used by these larvae is the small quantity of material available for analysis, being on the order of nanograms. In this work, we applied, for the first time, synchrotron radiation-based μ-X-ray fluorescence analysis (SR-μ-XRF) for in vivo and in situ analysis of young barnacles and barnacle cyprids. To obtain biologically relevant information relating to the body tissues, adhesives, and shell of the organisms, an in situ sample environment was developed to allow direct microprobe investigation of hydrated specimens without pretreatment of the samples. In 8-day-old juvenile barnacles (Balanus improvisus), the junctions between the six plates forming the shell wall showed elevated concentrations of calcium, potassium, bromine, strontium, and manganese. Confocal measurements allowed elemental characterization of the adhesive interface of recently attached cyprids (Balanus amphitrite), and substantiated the accumulation of bromine both at the point of initial attachment as well as within the cyprid carapace. In situ measurements of the cyprid cement established the presence of bromine, chlorine, iodine, sulfur, copper, iron, zinc, selenium, and nickel for both species. The previously unrecognized presence of bromine, iron, and selenium in the cyprid permanent adhesive will hopefully inspire further biochemical investigations of the function of these substances.
Published online: 29 December 2015
Im Titel wird mu als griechischer Buchstabe dargestellt
Gesehen am 05.05.2020